Are we moving into a new era for alcohol policy globally? An analysis of the Global Alcohol Action Plan 2022-30 - Jim McCambridge; Matthew Lesch (BMJ Global Health)
The Global Alcohol Action Plan 2022-30 (GAAP) represents an important milestone in policy implementation at the global level on alcohol and health. There has, however, been little attention paid to the GAAP in the research literature. With a focus on the alcohol industry, this analysis examines the content of, and prospects for, the GAAP. It is clear why stronger action on alcohol and health is needed. The health harming nature of alcohol and policy interference by industry are now clearly understood. The alcohol industry is now thus regarded primarily as a key part of the problem. The GAAP calls for action in six areas with specific roles for public health actors, and invites powerful industry actors to desist from harmful activities, within each area. The broad outline of what is expected of the alcohol industry is now clear. It remains unclear, however, how far countries will continue to face formidable opposition from the major alcohol companies and their surrogates, in adopting and implementing evidence-based measures. Governments must now act at speed, and it is unclear if the targets set for 2030 will be met. If this long-running public health policy failure continues, this will have dire consequences for low and middle income countries where the alcohol market is expanding. Stronger actions may also be needed.